THE RELATIONSHIP OF THE QUALITY OF NURSES' INTERPERSONAL COMMUNICATION IN NURSING CARE WITH THE LEVEL OF SATISFACTION OF INPATIENT PATIENTS - Dewi Anggraeni, Selviana (jfpublisher, 2025)
Introduction. Patient satisfaction is a feeling of joy or satisfaction that the product or service received meets or exceeds expectations, patient satisfaction is an indicator of the quality of services provided and patient satisfaction is capital to get more patients and to get loyal patients. One of the biggest factors in patient dissatisfaction is communication problems that arise when health workers seek information from patients when providing nursing care. Methods. The design of this research is cross sectional, where this type of research emphasizes the time of measurement/observation of independent and dependent variable data only once at a time. The population in this study was 293 respondents, the sample in this study was 169 inpatients, using a sampling technique cluster sampling. This research was conducted at Abdurrahman Syamsuri Paciran Lamongan Hospital. The research instrument uses a questionnaire sheet. This research was tested statistically using the Spearman rank (Rho) test. Result&Analysis. Based on the results of research using the Spearman statistical test with a significant level of a = 0.05, the result was p = 0.000, where the value of p < 0.05 can be concluded that H1 is accepted, which means there is a significant relationship between the quality of nursing interpersonal communication in nursing care and the level of patient satisfaction. hospitalized at Abdurrahman Syamsuri Paciran Lamongan Hospital. Discussion. This research was used as information for hospitals to maintain and improve the quality of nursing services provided to the community so that patient satisfaction is higher.